Parameter identification of Reed-Solomon codes over noisy environment - Swaminathan, Ramabadran (2020)
Blind reconstruction of code parameters plays a vital role in non-cooperative applications. It also provides additional advantages in applications such as adaptive modulation and coding, reconfigurable receivers, etc. In this paper, blind estimation algorithm is proposed to identify Reed-Solomon (RS) code parameters at the receiver over noisy channels. Simulation results validating the proposed algorithm are given for various test cases. Further, the accuracy of estimation of RS code parameters using the proposed algorithm is also evaluated for various M-ary quadrature amplitude modulation schemes. From the simulation results, it is observed that the accuracy of estimation improves with a decrease in code dimension and modulation order and the proposed algorithm outperforms other algorithms in the prior works.